Religious Behavior of Indonesian Muslims as Responses to the Covid-19 Pandemic - Mohammad Hidayaturrahman; Husamah Husamah; Sudarman Sudarman; Fitri Yanti; Ita Rahmania Kusumawati (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2021)
Covid-19 has become a world pandemic, and Indonesia is among the worse cases. Problems that arise are faced by all parties, including religious elites as well as laypeople. This study was conducted to describe how Muslims in Indonesia responded to and tried to cope with the Covid-19 pandemic. The study uses descriptive qualitative methods to collect data by observation, in-depth interview by phone, and online searching documents. From the research conducted, Islamic mass organizations have a relatively similar opinion that limits religious activities supported by various religious arguments. As for laypeople’s behavior, most are the same as mass organizations and Islamic leaders; very few have different behaviors. In anticipation of the virus spreading, most of them restricted religious activities in full by closing down the mosque and stopping public prayers. Few remained active as before the Covid-19 pandemic. Covid-19 telah menjadi pandemi dunia, dan Indonesia termasuk di antara kasus terparah. Permasalahan yang muncul dihadapi semua pihak, baik elit agama maupun awam. Kajian ini dilakukan untuk mendeskripsikan bagaimana umat Islam di Indonesia menanggapi dan berusaha mengatasi pandemi Covid-19. Penelitian ini menggunakan metode deskriptif kualitatif dengan pengumpulan data melalui observasi, wawancara mendalam melalui telepon, dan pencarian dokumen secara online. Dari penelitian yang dilakukan, ormas Islam memiliki pendapat yang relatif sama yaitu membatasi kegiatan keagamaan yang didukung oleh berbagai dalil keagamaan. Adapun perilaku orang awam, sebagian besar sama dengan ormas dan tokoh Islam; sangat sedikit yang memiliki perilaku berbeda. Untuk mengantisipasi penyebaran virus, sebagian besar dari mereka membatasi kegiatan keagamaan secara penuh dengan menutup masjid dan menghentikan sholat umum. Beberapa tetap aktif seperti sebelum pandemi Covid-19.